Development and validation of a combined hypoxia- and metabolism-related prognostic signature to predict clinical prognosis and immunotherapy responses in clear cell renal cell carcinoma - Wu, Xin; Xie, Wenjie; Gong, Binbin; Fu, Bin; Chen, Weimin; Zhou, Libo; Luo, Lianmin (Frontiers in Oncology, 2023)
Background: . Hypoxia and metabolism are closely correlated with the progression of cancer. We aimed to construct a combined hypoxia-and metabolism-related genes (HMRGs) prognostic signature to predict survival and immunotherapy responses in patients with clear cell renal cell carcinoma (ccRCC).The RNA-seq profiles and clinical data of ccRCC were acquired from the TCGA and the ArrayExpress (E-MTAB-1980) databases. Least absolute shrinkage and selection operator (LASSO), univariate and multivariate Cox regression analyses were applied to establish a prognostic signature. The E-MTAB-1980 cohort were selected for validation. Effectiveness and reliability of the signature was further evaluated by Kaplan-Meier (K-M) survival, time-dependent receiver operating characteristic (ROC). Further analyses, including functional enrichment, ssGSEA algorithm, CIBERSORT algorithm, and expression of immune checkpoints were explored to investigate immune status and immunotherapy responses.We constructed a prognostic 8-gene signature with IRF6, TEK, PLCB2, ABCB1, TGFA, COL4A5, PLOD2, and TUBB6. Patients were divided into high risk and low risk groups based on the medium-risk score. The K-M analysis revealed that patients in the high risk group had an apparently poor prognosis than those in the low risk group in the TCGA (p < 0.001) and E-MTAB-1980 (p < 0.005). The area under ROC curve (AUC) of the prognostic signature were 0.8 at 1 year, 0.77 at 3 years, and 0.78 at 5 years in the TCGA, respectively, and were 0.82 at 1 year, 0.74 at 3 years, and 0.75 at 5 years in the E-MTAB-1980, respectively. Independent prognostic analysis confirmed the risk score as a separate prognostic factor in ccRCC patients (p < 0.001). The results of ssGSEA not only shown a high degree of immune cell infiltration but also high scores of immune-related functions in the high risk group.The CIBERSORT analysis further confirmed that the abundance of immune cell were apparently different between two risk groups. The risk score was significantly correlated with expression of Cytotoxic T Lymphocyte-Associated Antigen-4 (CTLA4), Lymphocyte-activation gene 3 (LAG3) and Programmed cell death protein 1 (PD-1).The HMRGs signature could be used to predict clinical prognosis, evaluate efficacy of immunotherapy, and guide personalize immunotherapy in ccRCC patients.